1996
DOI: 10.1002/(sici)1097-0339(199603)14:2<101::aid-dc1>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Role of immunocytochemistry, electron microscopy, and DNA analysis in fine-needle aspiration biopsy diagnosis of Wilms' tumor

Abstract: We reviewed the cytologic features and results of ancillary studies in eight fine‐needle aspiration biopsies (FNAB) performed by posterior approach in 8 patients with unresectable Wilms' tumor (WT). Chemotherapy was given following the FNAB diagnosis of WT, which was confirmed subsequently by histologic examination of surgically resected specimens. Indications for FNAB included: unresectable tumor, bilateral disease, initial presentation with metastatic disease, uncertainty regarding tumor site, and documentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…Reports on clinically useful markers are not available. NSE (neuron-specific enolase) is useful in the initial screening for neuroblastoma, but the finding of elevated serum NSE levels does not exclude the diagnosis of Wilms' tumour (Pritchard et al, 1987), which is also well demonstrated immunohistochemically (Ellison et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports on clinically useful markers are not available. NSE (neuron-specific enolase) is useful in the initial screening for neuroblastoma, but the finding of elevated serum NSE levels does not exclude the diagnosis of Wilms' tumour (Pritchard et al, 1987), which is also well demonstrated immunohistochemically (Ellison et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokeratin expression has been described mainly for cells of epithelial origin. The cytokeratin phenotype is well described in C) Cancer Research Campaign 1998 fetal kidney and is thought to be similar in the tubules of nephroblastoma (Giovagnoli et al, 1994;Ellison et al, 1996;Sainio et al, 1997). Only a few investigators have reported high serum TPS levels in cytokeratin-negative tumours (Norton et al, 1987;Ramaekers et al, 1988;Liu et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of anaplasia on cytology is made when a smear shows extremely large hyperchromatic blastemal cells three times the size of the surrounding blastemal cells coupled with brisk atypical mitosis (fig 2D). A potential limitation of FNAC of Wilms’ tumour is the inability to extensively sample a large mass and thereby to detect anaplasia1 and to distinguish focal from diffuse anaplasia.…”
Section: Steps In the Cytological Evaluation Of Paediatric Renal Tumoursmentioning
confidence: 99%
“…Needle aspirates can easily be fixed in Karnosky or Universal fixative and the sediments can be processed for examination of specific ultrastructural features. Electron microscopy is particularly useful in identifying neuroblastoma and differentiating it from a Wilms’ tumour 1. While cell processes, dense-core granules and neurotubules are features that indicate a neuroblastoma, Wilms’ tumour reveals cell junctions, microvilli, flocculent basement membrane-like material, cilia and autophagolysosomes 1.…”
Section: Steps In the Cytological Evaluation Of Paediatric Renal Tumoursmentioning
confidence: 99%
See 1 more Smart Citation